(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The debate concerning the living will and its adoption in clinical practice have taken an echo also in the political arena and in the media context. The ethical and clinical perspective has highlighted some important limitations of the living will, to be taken into account when this decision-making tool is incorporated into clinical practice. In particular, in spite of the fact that the living will is used to lead the doctor-patient relationship to greater patient autonomy, in medical practice it becomes a rather questionable document, which sometimes confuses the medical decision-making. Best suited to the nature and characteristics of the patient-physician relationship seems to be the tool of the "advance care planning". This decision making process is eligible to be an informed expression of will; also he sees the participation of all stakeholders in the clinical setting, in view of a shared decision-making process, safeguarding both the patient’s self-determination and the independence caregivers.